2012
DOI: 10.3109/08037051.2012.732761
|View full text |Cite
|
Sign up to set email alerts
|

Metformin reduces vascular endothelial dysfunction caused by an acute glucose load in patients with hypertension

Abstract: Metformin can prevent transient endothelial dysfunction caused by acute glucose load in patients with PH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
5
0
2
Order By: Relevance
“…Preclinical in vivo studies and clinical data suggest that metformin possesses pleiotropic effects that protect the endothelium (Mather et al, 2001;Zhang et al, 2013;Arunachalam et al, 2014;Kinaan et al, 2015). However, the effect of metformin on miR-34a and its impact on endothelial function have not previously been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical in vivo studies and clinical data suggest that metformin possesses pleiotropic effects that protect the endothelium (Mather et al, 2001;Zhang et al, 2013;Arunachalam et al, 2014;Kinaan et al, 2015). However, the effect of metformin on miR-34a and its impact on endothelial function have not previously been studied.…”
Section: Discussionmentioning
confidence: 99%
“…(), it is of particular interest that Zhang et al . () have reported that a single 500 mg dose of metformin prevents the reduction of brachial artery FMD following an oral glucose load in patients with primary hypertension. Collectively, these data from a combination of clinical and in vitro studies strongly suggest that metformin does have a direct endothelial protective action that is most likely, at least in part, mediated via eNOS and, possibly, involving an antioxidant action and can have a rapid onset of action as reflected by the data presented by Zhang et al .…”
Section: Cellular Mode Of Action: Role Of Amp Kinase (Ampk)mentioning
confidence: 99%
“…Fourteen of these articles reported vascular data for multiple subgroups of a given or diverse health status; thus, they were assessed as individual studies. 22,[25][26][27][28]31,37,38,45,52,[56][57][58][59] The main characteristics and clinical data for these studies are shown in Tables 1 and 2, respectively. Three potentially relevant studies were not available for full text reading and thus could not be included.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%